Enhancing solar power generation with a bifacial dual-axis parabolic dish tracking prototype - Kalhoro, Sabir Ali; Rahimoon, Asif. A.; Abdullah, Mohd Noor; Mohd Yassim, Halyani; Raza, Asif; Soomro, Shafique A. (2024)
Photovoltaic (PV) modules often suffer from defects like glass breakage, soiling, discoloration, hotspots, reducing their power generation efficiency. Fixed-angle PV systems are increasingly being replaced by single axis tracking system (STs) and dual axis tracking system (DTs) mode of operation to enhance generation. However, STs improve performance by following daily solar motions but struggle with seasonal adjustments. While DTs overcome this limitation by enabling precise two-axis tracking, capturing optimal solar irradiance. The bifacial configured PV modules further boost generation efficiency by utilizing radiation from both sides, offering flexibility in orientation and reducing tracking limitations. The primary objective of this study is to enhance power generation from the bifacial PV module. Hence, this study is proposing a cost-effective bifacial dual-axis parabolic dish tracker with a closed-loop design. The system employs Light Dependent Resistor (LDR) sensors and a Raspberry Pi controller to achieve precise dual-axis tracking assembled on stainless frame. The size of parabolic dish is comprised of aluminum foil polished around 4×4ft area. The proposed study was tested over three days in November along with an albedo of approximately 0.39 value. The obtained result shows that generated cumulative power in watt (W) was recorded as 402.47 W,418.06 W and 427.30 W respectively. Thus, results demonstrate the combined potential of bifacial PV modules and DTs scheme has efficiently improved the power generation.